The problematic separation of text and context: A comprehensive study in textual and cultural interaction - Loucif, Fouad; Azzedine, Ben Azeiz; Khadidja, Ben Halima (The International tax journal, 2026)
This research addresses a fundamental issue in critical and linguistic studies: the relationship between text and context, and the extent to which a text is autonomous from the circumstances of its production. The study critically examines divergent theoretical approaches. On one hand, schools such as Structuralism and Formalism focused on the text as a closed and self-sufficient linguistic structure, arguing that meaning emerges from the text’s internal relations. On the other hand, approaches such as Pragmatics and Cultural Criticism—particularly in the works of prominent thinkers like Edward Said and Michel Foucault—assert that meaning cannot be separated from the complex network of social, political, and cultural contexts that shape and govern its interpretation. Through the analysis of these positions, the study investigates the profound impact of context on understanding literary and communicative texts, attempting to balance the role of a text’s internal structure with external factors in the production of meaning. It also discusses the methodological implications of the problematic separation of text and context and its direct effect on discourse analysis. Ultimately, the research seeks to answer a central question: Can an objective reading of a text be achieved in isolation from its context,,,